Planned earlier delivery for late pre-eclampsia may be better for mothers. (15th January 2020) - Cook, Rob; Lyon-Maris, Johnny; Davidson, Peter
The study: Chappell LC, Brocklehurst P, Green ME, et al. Planned early delivery or expectant management for late preterm pre-eclampsia (PHOENIX): a randomised controlled trial. Lancet 2019;394:1181-90. This project was funded by the NIHR Health Technology Assessment Programme (project number 12/25/03). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000838/mothers-benefit-from-a-planned-earlier-delivery-for-late-pre-eclampsia